Development of an epitope panel for consistent identification of antigen‐specific T‐cells in humans. Issue 2 (3rd July 2017) - Fløe, Andreas; Løppke, Caroline; Hilberg, Ole; Wejse, Christian; Brix, Liselotte; Jacobsen, Kivin
Summary: We aimed to establish a panel of MHC–peptide multimers suitable as a positive control in the detection of HLA A*0201 restricted antigen specific T cells (ASTC) by flow cytometry. MHC Dextramers were loaded with HLA A*0201 binding peptides from viral antigens and melanoma targets identified from a literature search and in silico prediction. Peripheral blood mononuclear cells (PBMC) from healthy donors were analysed with the MHC Dextramers using flow cytometry. The best performing epitopes were tested on PBMC from patients undergoing testing for Mycobacterium tuberculosis infection to assess the coverage of this epitope panel. Of 21 candidate epitopes, ASTC could be detected against 12 (57·1%) in at least one of 18 healthy blood donors. Reactivity to two or more epitopes was seen in 17 of the 18 donors (94·4%). We selected the six best‐performing epitopes and demonstrated a positive response in 42 (97·7%) of 43 patient samples (healthy, latent and active M. tuberculosis infection). The selected panel of six antigenic epitopes sufficed as a positive control in the detection of ASTC in HLA A*0201. Performance was robust in different stages of latent and active M. tuberculosis infection, indicating reliability also during infection. Abstract : MHC multimer‐based detection of antigen‐specific T cells ex vivo is limited by a lack of reliable controls. Using a pool of six MHC Dextramers presenting viral epitopes as well as a melanoma–epitope yields a coverage of > 97% as a positive control in HLA A*0201. The coverage is robust across different age groups, and in both healthy persons and patients with tuberculosis.